2013
DOI: 10.1021/ja4032538
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Multiple Oxidative Equivalents at a Single Site by Cross-Surface Electron Transfer on TiO2

Abstract: The photodriven accumulation of two oxidative equivalents at a single site was investigated on TiO2 coloaded with a ruthenium polypyridyl chromophore [Ru(bpy)2((4,4'-(OH)2PO)2bpy)](2+) (Ru(II)P(2+), bpy = 2,2'-bipyridine, ((OH)2PO)2-bpy = 2,2'-bipyridine-4,4'-diyldiphosphonic acid) and a water oxidation catalyst [Ru(Mebimpy) ((4,4'-(OH)2PO-CH2)2bpy)(OH2)](2+) (Ru(II)OH2(2+), Mebimpy = 2,6-bis(1-methylbenzimidazol-2-yl)pyridine, (4,4'-(OH)2PO-CH2)2bpy) = 4,4'-bis-methlylenephosphonato-2,2'-bipyridine). Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 57 publications
2
78
0
1
Order By: Relevance
“…The back‐ET from TiO 2 (e − ) to catalyst on the surface is often the main interfacial recombination pathway, leading to shorter recombination time and lower efficiency of DSPEC devices . Meyer and co‐workers reported that the ET from their ruthenium catalyst [Ru II OH 2 ] 2+ bound to TiO 2 ( 8 in Figure ) to the photooxidized chromophore [Ru III P] 3+ occurs within 20 ns, whereas the interfacial back‐ET from TiO 2 (e − ) to both [Ru III P] 3+ and [Ru III OH 2 ] 3+ under these conditions was rate‐limited by electron transport dynamics within the TiO 2 and occurs on similar time scales ( t 1/2 ≈0.3–0.5 μs) . To suppress unwanted recombination, the following processes are effective: 1) hindrance of the recombination from TiO 2 (e − ) to WOCs and S .+ , 2) acceleration of the intermolecular ET reaction from a WOC to S .+ on the surface, and 3) acceleration of electron transport within the TiO 2 .…”
Section: Visible‐light‐driven Water Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…The back‐ET from TiO 2 (e − ) to catalyst on the surface is often the main interfacial recombination pathway, leading to shorter recombination time and lower efficiency of DSPEC devices . Meyer and co‐workers reported that the ET from their ruthenium catalyst [Ru II OH 2 ] 2+ bound to TiO 2 ( 8 in Figure ) to the photooxidized chromophore [Ru III P] 3+ occurs within 20 ns, whereas the interfacial back‐ET from TiO 2 (e − ) to both [Ru III P] 3+ and [Ru III OH 2 ] 3+ under these conditions was rate‐limited by electron transport dynamics within the TiO 2 and occurs on similar time scales ( t 1/2 ≈0.3–0.5 μs) . To suppress unwanted recombination, the following processes are effective: 1) hindrance of the recombination from TiO 2 (e − ) to WOCs and S .+ , 2) acceleration of the intermolecular ET reaction from a WOC to S .+ on the surface, and 3) acceleration of electron transport within the TiO 2 .…”
Section: Visible‐light‐driven Water Oxidationmentioning
confidence: 99%
“…[92] Meyer andc o-workers reported that the ET from their ruthenium catalyst[ Ru II OH 2 ] 2 + bound to TiO 2 (8 in Figure6)t ot he photooxidizedc hromophore [Ru III P] 3 + occurs within 20 ns, whereas the interfacial back-ETf rom TiO 2 (e À )t ob oth[ Ru III P] 3 + and [Ru III OH 2 ] 3 + under these conditions was rate-limited by electron transport dynamics within the TiO 2 andoccurs on similar time scales (t 1/2 % 0.3-0.5 ms). [93] To suppress unwanted re-combination,t he following processes are effective:1 )hindranceo ft he recombination from TiO 2 (e À )t oW OCs and SC + , 2) acceleration of the intermolecularE Tr eaction from aW OC to SC + on the surface, and3 )acceleration of electron transport within the TiO 2 .I nt he case of ah eterogeneous inorganic catalyst for water oxidation, the introductiono fathin layer of metal oxide between the catalyst and wide-bandgapi norganic semiconductor will hinder the interfacial back-ET. [92,94] In the case of am olecular catalyst, as ystematic change in the spacer length by an organic synthetic method leads to ah ighere fficiency.S un and co-workers reported their catalysts immobilized on TiO 2 with different length of spacers, and demonstrated that the slower back-ET indeed improvesthe total efficiency of the system.…”
Section: Recombination To Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…A DS-PEC device using TiO 2 (1+2) as working electrode (WE) exhibits better performance than TiO 2 (1+3) as WE in light-driven water splitting. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Our group recently reported several DS-PECs, in which molecular photosensitizer (PS) 1 and molecular ruthenium catalysts were co-adsorbed onto TiO 2 -sintered fluoride-doped tin oxide (FTO) glass (Scheme 1). Solar energy is considered an ideal energy source to avoid the greenhouse effect and to meet the energy demands of the future.…”
Section: High-performance Photoelectrochemical Cells Based On a Binucmentioning
confidence: 99%
“…[1][2][3] Most photoanodes used in DSPECs utilize Ru polypyridine chromophores and a water oxidation catalyst or covalently linked chromophore-catalyst assemblies bound to mesoporous wide bandgap metal oxide semiconductor films. [4][5][6][7][8] In spite of considerable synthetic efforts directed to the construction of chromophore and catalyst assemblies, only linkers such as phosphonate and carboxylate groups, which form a covalent bond to the oxide surface (generally TiO 2 ), have been explored. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 2 Layer-by-layer (LbL) polyelectrolyte self-assembly involves the sequential deposition of oppositely charged polymers to build up multilayer polymer structures that feature a tailored nanostructure that can be defined by the polyelectrolyte structures and sequence used during multilayer construction.…”
mentioning
confidence: 99%